Strategi Lembaga Pendidikan Anak Usia Dini dalam Melibatkan Guru Laki-Laki - Hayati, Miratul; Yubaedi Siron; Hermawati, Erma (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2021)
The involvement of male teachers in Early Childhood Education (ECE) institutions is still a matter of debate. Data for the last 10 years shows a decrease in the number of male teachers in ECE institutions. Even though their involvement is as a substitute figure for their father at school. This study aims to determine the strategy carried out at ECE institutions in KB-TK Al-Fath Cirendeu in involving male teachers. This research uses a qualitative approach with a case study method. The research subjects included: the principal, 2 female teachers and 7 male teachers. Data collection was carried out employing observation, in-depth interviews and documentation. Data analysis using Miles Huberman through the stages of data reduction, data presentation, verification, and concluding. The results of the study found that the ECE institutional strategy to involve male teachers in the institution was carried out through the planning of male teacher involvement objectives, recruitment plans, provision of special facilities, preparation of organizational structures, division of job descriptions between male and female teachers and institutional supervision of male teacher performance.